Simple characterization by the influence of dammar in polyurethane as a coating resin / Mohd Arif Md Nor - Md Nor, Mohd Arif (2013)
In this project, the dammar is used to modified and improve the properties of polyurethane (PU) as a coating resin. The dammar was varied from 10wt% to 50wt% to optimize the composition. After the sample was cured, this sample was been testing to find the best composition in which good adhesion, higher contact angle and resistivity. The adhesion was measured using cross hatch test (ASTM D3359), result found that PU-10wt% of dammar showed the best adhesion compared to others. Electrochemical impedance spectroscopy (EIS) is a corrosion tool to measured resistivity. After the sample was undergone this characterization, it was found that PU-10wt% of dammar showed the higher resistivity, which is 4.98xl06C3. While other compositions, in a range of 1.0xl04O until 1.0xl06O. Wettability was measured using contact angle instrument. The biggest angle shown by PU-20wt% of dammar (66.19°) followed by PU-10wt% of dammar (64.31°), both are almost reach 90° of angle. This value can categorize the PU-20wt% of dammar and PU-10wt% of dammar as water resistance coating. Overall, thePU with 10wt% of dammar showed the best composition with good adhesion, resistivity and wettability. This means 10wt% of dammar can modify the PU to be a good performance resin.